Introduction to Mathematical Analysis, An. - Shirali, Satish (Alpha Science International, 2013)
AN INTRODUCTION TO MATHEMATICAL ANALYSIS is an elementary text on the theory of functions of one real variable and is intended for students with a good understanding of calculus. It is supposed to replace traditional and outmoded courses in mathematical analysis. The book begins with material on the real number system as a Dedekind complete ordered field, continuous functions, sequences and series of constant terms as well as of functions. Pointwise and uniform convergence of series of functions, power series, treatment of trigonometric and exponential functions in terms of series are discussed.